A Block-Based Environment for Teaching Parallel Programming with OpenCL - Gomes Júnior, Josué da Silva; Pereira, Maelso Bruno Pacheco Nunes; Brito, Alisson V.; Ramos, Jorge Gabriel Gomes de Souza (International Journal of Computer Architecture Education, 2016)
This work presents the educational software Blockly OpenCL. It aims to assist in the teaching-learning of the programming paradigm for parallel architectures with OpenCL. It uses the visual programming paradigm through a block-based development environment created with the Google Blockly API, allowing users to create applications by manipulating blocks and exporting them to OpenCL C++. Blockly OpenCL also includes a web page containing contextual information about the tool, examples, and support materials on OpenCL.